Pemberdayaan Masyarakat melalui Minuman Fermentasi Herbal di Kawasan Hutan guna Peningkatan Kesehatan dan Pendapatan KTH Pujon Hill Malang, Jawa Timur - Waskitho, Nugroho Tri; Ramadhan, Ramli; Sukardi (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
This community empowerment program collaborated with the Pujon Hill Forest Farmers Group (KTH) in Bendosari Village, Pujon, Malang, to empower farmers in utilizing local medicinal plants to produce fermented herbal drinks. Activities included socialization, training, fermentation process demonstrations, and participatory evaluation. A total of 80 participants were involved in this program. The results showed an increase in knowledge and practical skills in the cultivation and processing of medicinal plants, the successful production of fermented herbal beverage prototypes, and a clear interest in continuing production. Many participants reported chronic health complaints (e.g., fatigue, hypertension, joint pain), indicating community demand for functional herbal beverages. This program demonstrates the potential to improve community health awareness and household income. Recommendations include improving quality control, packaging, and market relations to ensure sustainability.